2022
DOI: 10.3390/s22052033
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ag on the Limit of Detection towards NH3-Sensing in Spray-Coated WO3 Thin-Films

Abstract: Ag-doped WO3 (Ag–WO3) films were deposited on a soda-lime glass substrate via a facile spray pyrolysis technique. The surface roughness of the films varied between 0.6 nm and 4.3 nm, as verified by the Atomic Force Microscopy (AFM) studies. Ammonia (NH3)-sensing measurements of the films were performed for various concentrations at an optimum sensor working temperature of 200 °C. Enrichment of oxygen vacancies confirmed by X-ray Photoelectron Spectroscopy (XPS) in 1% Ag–WO3 enhanced the sensor response from 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The LOD for LPG at ∼229 ppm was within the reported range of 200–1000 ppm for the LPG MQ-6 sensor . Anusha et al reported a LOD of 500 ppb at a working temperature of 200 °C for their Ag–WO 3 films prepared by the spray pyrolysis method.…”
Section: Resultssupporting
confidence: 64%
“…The LOD for LPG at ∼229 ppm was within the reported range of 200–1000 ppm for the LPG MQ-6 sensor . Anusha et al reported a LOD of 500 ppb at a working temperature of 200 °C for their Ag–WO 3 films prepared by the spray pyrolysis method.…”
Section: Resultssupporting
confidence: 64%
“…25 nm. In the structures where the channel is given as a continuous oxide film, the response is lower at 100 • C by a few orders [51]. Although the estimate of the WO 3 response in the SWCNT40-WO 3 structure under study is still lower than the best response known from the literature for this material, the fabricated structure exhibits a substantially lower response time, being of ca.…”
Section: The Characterization Of Gas-sensing Performance Of the Senso...mentioning
confidence: 77%
“…14 In recent years, there has been a significant focus on developing novel mixed oxides rather than traditional mixed binary oxides, such as tungstate, ferrites, cobaltates, and stannates. 25,26 Zinc tungstate (ZnWO 4 ) belongs to the metal tungstate family and exhibits significant potential in a range of applications, such as photoluminescence, microwave technologies, optical fibers, and environmental applications. 27,28 Numerous studies have demonstrated the efficiency of composite materials in gas sensing applications, implying that enhanced performance can be achieved by the synergistic interaction between different metal oxides.…”
Section: Introductionmentioning
confidence: 99%